The Extract of Sonneratia apetala Leaves and Branches Ameliorates Hyperuricemia in Mice by Regulating Renal Uric Acid Transporters and Suppressing the Activation of the JAK/STAT Signaling Pathway - Wu, Yu-Lin; Chen, Jin-Fen; Jiang, Lin-Yun; Wu, Xiao-Li; Liu, Yu-Hong; Gao, Chang-Jun; Wu, Yan; Yi, Xiao-Qing; Su, Zi-Ren; Cai, Jian; Chen, Jian-Nan (Frontiers in Pharmacology, 2021)
Sonneratia apetala Buch.-Ham., an exotic mangrove species with antidiabetic, antibacterial and antioxidant capacities, mainly distributes in the southeast coastal areas in China. The present work investigated the protective effects of Sonneratia apetala leaves and branches extraction (SAL) on hyperuricemia (HUA) in mice. Potassium oxonate (PO) and hypoxanthine (HX) were used to establish the HUA model by challenge for consecutive 7 days. Results revealed that SAL inhibited the increases in kidney weight and index compared to Vehicle group. Meanwhile, SAL significantly decreased the levels of uric acid (UA), creatinine (CRE) and blood urea nitrogen (BUN) in serum. Additionally, SAL inhibited the activity of xanthine oxidase (XOD) in the liver. SAL ameliorated PO and HX-induced histopathological changes. Moreover, it regulated oxidative stress markers including malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD) activity and glutathione (GSH) content. Also, SAL inhibited the increases in renal levels of interleukin-6 (IL-6), interleukin-18 (IL-18), interleukin-1β (IL-1β), tumor necrosis factor (TNF-α), monocyte chemotactic protein 1 (MCP-1) and transforming growth factor-β (TGF-β). SAL remarkably reduced suppressor of cytokine signaling 3 (SOCS3), janus kinase 2 (JAK2) and subsequent phosphorylation of signal transducer and activator of transcription 3 (STAT3) expression. In addition, SAL inhibited the activation of nuclear factor kappa-B (NF-κB) in the kidney. Furthermore, SAL protected against HUA by regulating renal UA transporters of organic anion transporter (OAT1), urate reabsorption transporter 1 (URAT1) and glucose transporter 9 (GLUT9). These findings suggested that SAL ameliorated HUA by inhibiting the production of uric acid and enhancing renal urate excretion, which are related to oxidative stress and inflammation, and the possible molecular mechanisms include its ability in to inhibit JAK/STAT signaling pathway. Thus, SAL might be developed into a promising agent for HUA treatments.